Factors Affecting Resilience in Families of Adults With Diabetes. (June 2016) - Batty, Kristine E.; Fain, James A.
Purpose: The purpose of the study was to investigate the impact of family resilience on families of adults with type 1 or type 2 diabetes. Methods: A convenience sample of 77 participants was recruited from several diabetes education/support group programs and 1 private medical practice to participate in this descriptive correlational study. Participants completed several instruments measuring family member satisfaction with components of family functioning, family resilience, life orientation (measure of optimism), and diabetes knowledge. Results: Family members were predominantly female (71%) and white (97%), and they had a minimum of a college education (79%). A significant positive relationship was found between family functioning and family resilience ( r = 0.59, P < .01). Regression analysis revealed that family functioning was the only predictor of family resilience, explaining 46% of the variance. Positive outlook and diabetes knowledge were not significant contributors to the model. A significant low correlation was found between family member's level of diabetes knowledge and measure of optimism. Additional findings demonstrated that the Family Resilience Assessment tool was a reliable measure, with a Cronbach alpha of 0.91. Conclusion: Family functioning was associated with family resilience. Future research should focus on replicating the study in a more heterogeneous population, with further investigation into the needs of family members of adults with diabetes.